1991
DOI: 10.1161/01.hyp.17.6.1038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an angiotensin II and a kinin receptor antagonist on the renal hemodynamic response to captopril.

Abstract: The role of angiotensin II and kinins on the renal cortical and papillary hemodynamic and on the sodium and water excretory responses to converting enzyme inhibition with captopril was examined in euvolemic Munich-Wistar rats. Cortical and papillary blood flows were measured using a laser Doppler flowmeter. Cortical blood flow increased 28% after blockade of angiotensin II receptors with DuP 753 (2 mg/kg i.v., n=6). Captopril (2 mg/kg i.v., n=6) had no effect on cortical blood flow in rats pretreated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…We have observed that rats pretreated with a cyclooxygenase inhibitor (meclofenemate) exhibited a significant reduction of medullary flow with subpressor intravenous infusion of ANG II (61). Similar responses have been observed with kinin receptor antagonists (24,99). It has now also been found that the hemoxygenase enzymes are present at significantly greater concentrations in the renal medulla than in the cortex, and the production of medullary CO via the hemoxygenase pathway may participate in the control of flow to this region (134).…”
Section: Renal Medullary No Protects Against Chronic Ang Ii- Ne- Ansupporting
confidence: 55%
“…We have observed that rats pretreated with a cyclooxygenase inhibitor (meclofenemate) exhibited a significant reduction of medullary flow with subpressor intravenous infusion of ANG II (61). Similar responses have been observed with kinin receptor antagonists (24,99). It has now also been found that the hemoxygenase enzymes are present at significantly greater concentrations in the renal medulla than in the cortex, and the production of medullary CO via the hemoxygenase pathway may participate in the control of flow to this region (134).…”
Section: Renal Medullary No Protects Against Chronic Ang Ii- Ne- Ansupporting
confidence: 55%
“…33 -3841 For most of these studies, however, the very high levels reported for circulating immunoreactive kinins raise questions concerning the validity of their estimation. 12 Indirect evidence for a role of BK-(1-9) in mediating some of the effects of ACE inhibitors has come from the use of BK-(l-9) antagonists, kinin antibodies, and aprotinin, which partially reverse the hypotensive effect of ACE inhibitors 79 -42 - 48 and also partially reverse the effects of ACE inhibitors on renal papillary blood flow, urine flow, and sodium excretion 49 -50 on cardiac hypertrophy 11 and on neointima formation. 13 In the present study perindopril administration increased BK-(l-9) levels in blood and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ACE inhibitors also favor the accumulation of kinins by preventing their degradation (10). In addition, compelling evidence suggests the involvement of kinins in the renal effects of ACE inhibitors (22,39), and Tschöpe et al (48) have shown that kidney B 2 R is upregulated in streptozotocin (STZ)-diabetic rats. Nevertheless, the roles of BK and B 2 R in the protective effects of ACE inhibitors during the development of DN remain to be established.…”
mentioning
confidence: 99%